CHARACTERISTICS OF THE STRUCTURAL COMPONENTS OF PROJECT COMPETENCE OF BACHELOR STUDENTS IN VOCATIONAL EDUCATION (TRANSPORT) - KOVALCHUK, Bohdan (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2026)
The article reveals the holistic structure of project competence as a fundamental component of professional competence for bachelors of vocational education (transport), ensuring their readiness for successful design-engineering and organizational-technological activities amid contemporary industry challenges. Project competence of bachelors of vocational education (transport) is considered as an integrated quality reflecting the ability to carry out purposeful, scientifically grounded, and technologically correct project activities in the professional-pedagogical and transport fields. The structural components of project competence for bachelors of vocational education (transport) are identified as follows: motivational-value component – determines students’ intrinsic readiness for project activities and their attitude toward the profession; cognitive component – characterizes the system of knowledge required for professional project work in the transport sector; operational-activity component – practical readiness of students to perform project tasks of varying complexity; reflective-evaluative component – reflects the ability to analyze the quality of one’s project activity, evaluate the effectiveness of implemented solutions, and determine directions for improvement. Considering the structure of project competence, the stages of its formation are proposed: motivational stage (consolidating future vocational teachers’ need to master project activities), informational stage (forming ideas about project activities, prospects, and opportunities for applying the project method in professional-pedagogical practice in the transport sector), activity stage (practical application of acquired knowledge and active engagement in project work), and evaluative stage (monitoring the dynamics of project competence development, identifying existing gaps, and minimizing them). It is concluded that developed project competence ensures the readiness of bachelors of vocational education (transport) for independent engineering and pedagogically oriented decision-making, optimization of transport processes, introduction of innovations in training qualified workers for the transport sector, and performing professional activities under the conditions of dynamic development of transport infrastructure and modern technologies.